Improving Critical Thinking Skills in History - Carl Kosta Savich (Networks: An Online Journal for Teacher Research, 2009)
This action research project, conducted by a classroom teacher, investigated strategies and techniques to improve critical thinking skills and engagement in a high school history classroom. The research methods involved comparing quiz, test, and essay scores as well as student surveys, interviews and teacher-created field notes from inquiry-based and lecturebased classrooms. The inquiry classroom involved role-playing, simulations, re-enactments, multiple text analysis, and oral/visual presentations. Students engaged in analyzing bias, examining different viewpoints and perspectives, and analyzing documents. The findings indicate that when critical thinking skills were emphasized and integrated in lesson planning, students achieved higher scores on tests, quizzes, and assignments and gained a deeper and more meaningful understanding of history.